Cujo - King, Stephen, 1947-; Manicki, Jacek (Warszawa : Proszynski i S-ka, 2000)
Polish translation of "Cujo". A chilling horror novel about a rabid dog intimidating a neighborhood.
Translation of: Cujo.
Keywords: Rabies -- Fiction; Dogs -- Fiction